Respuesta :

Answer:

[tex]\dfrac{(-5)3x^7(yz)^4}{(3)2x^2y^8z^2}=\dfrac{-5x^5z^2}{2y^4}[/tex]

Step-by-step explanation:

Given:

The expression to simplify is given as:

[tex]\frac{(-5)3x^7(yz)^4}{(3)2x^2y^8z^2}[/tex]

In order to simplify this, we have to use the law of indices.

1. [tex](ab)^m=a^mb^m[/tex]

So, [tex](yz)^4=y^4z^4[/tex]

Substitute this value in the above expression. This gives,

[tex]=\dfrac{(-5)3x^7y^4z^4}{(3)2x^2y^8z^2}\\\\\\=\dfrac{-15x^7y^4z^4}{6x^2y^8z^2}......(-5\times 3=15\ and\ 3\times 2=6)[/tex]

Now, we use another law of indices.

2. [tex]\frac{a^m}{a^n}=a^{m-n}[/tex]

So,  [tex]\frac{x^7}{x^2}=x^{7-2}=x^5,\frac{y^4}{y^8}=y^{4-8}=y^{-4}, \frac{z^4}{z^2}=z^{4-2}=z^2[/tex]

Substitute these values in the above expression. This gives,

[tex]=\frac{-15}{6}\times x^5\times y^{-4}\times z^2\\\\=\frac{-5x^5y^{-4}z^2}{2}[/tex]

Finally, we further simplify it using the law [tex]a^{-m}=\frac{1}{a^m}[/tex]

So, [tex]y^{-4}=\frac{1}{y^4}[/tex]

Therefore, the given expression is simplified as:

[tex]\dfrac{(-5)3x^7(yz)^4}{(3)2x^2y^8z^2}=\dfrac{-5x^5z^2}{2y^4}[/tex]